The Silver Coins of the Aksumite King Meḥadeyos in the Light of the Chemical-Physical Analyses - Pedroni, Luigi; Devoto, Guidi (Aethiopica, 2003)
Recently it was possible to examine a struck and a cast silver coin issued by the Aksumite king Mehadeyos (ca. 420/430 A.D.) typologically similar to the cast type Munro-Hay AR 1. The chemical-physical analyses carried out on these Aksumite coins – the cast specimen and the minted one – from a side show a substantial convergence with those realised by others, but they diverge for the aspect regarding their authenticity. In actual fact the minted coin is an obvious counterfeit because the chemical composition of the alloy contains silver (92/93%) in a percentage never attested in the contemporary Aksumite coinage whereas the cast specimen has been proved to be ancient and made of good silver and copper alloy (85%), typical of the Aksumite coinage in the 5th century A.D. Furthermore its microcrystalline structure and the concretions developed over hundreds of years eliminate all doubts about a hypothetical remelting of the coin in modern times. ATTENTION: Due to copy-right no online publication is provided.